Emerging obesity among preschool-aged Canadian Inuit children: results from the Nunavut Inuit Child Health Survey ... - Galloway, Tracey; Young, T. Kue; Egeland, Grace M. (University of Alberta Library, 2010)
"Objectives: The study goal was to evaluate the growth status of preschool-age Canadian Inuit children. Study design: As part of a larger study of population health across the Canadian High Arctic, the International Polar Year Inuit Health Survey collected growth and nutrition data on 388 children aged 3 to 5 years. Methods: Data collection included anthropometric measures, health history, food frequency and 24-hour recall. Height and BMI were compared with the 2000 Centers for Disease Control and Prevention (CDC) growth reference (1); 24-hour recall and FFQ results were tabulated to produce daily and monthly frequencies of consumption of market and country foods." (as cited in abstract) ...